2014
DOI: 10.15353/joci.v10i1.2681
|View full text |Cite
|
Sign up to set email alerts
|

Internet Access At Public Access Venues In A Developing Countries: Lessons from Yogyakarta, Indonesia

Abstract: This paper aims to present differences between male and female internet users in terms of their internet access, including the information they seek, their ICT uses, their frequency of use, and their barriers. This paper reports data from 400 internet café users in urban and non-urban areas in Yogyakarta, Indonesia.The results show that there were some differences between the male and female users. Firstly, the number of male users who visited in internet café was slightly higher than that of female users. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…In a review of empirical research on the impacts of public access to ICTs, Sey and Fellows (2011) found that young men with high socio-economic status were the predominant users of telecentres. These results are similar to the findings of other studies in Indonesia (Wijaya and Polina, 2014), Colombia (Amariles et al , 2006b) and Malawi (Kapondera, 2014; Kapondera and Chigona, 2017a, 2017b). As ICT can offer potential benefits to empower women to reach their objectives, it is important to understand the perception and usage behaviour of telecentres among rural women.…”
Section: Introductionsupporting
confidence: 92%
“…In a review of empirical research on the impacts of public access to ICTs, Sey and Fellows (2011) found that young men with high socio-economic status were the predominant users of telecentres. These results are similar to the findings of other studies in Indonesia (Wijaya and Polina, 2014), Colombia (Amariles et al , 2006b) and Malawi (Kapondera, 2014; Kapondera and Chigona, 2017a, 2017b). As ICT can offer potential benefits to empower women to reach their objectives, it is important to understand the perception and usage behaviour of telecentres among rural women.…”
Section: Introductionsupporting
confidence: 92%
“…A study conducted by Sey and Fellows (2011) reported that telecentre users followed traditional lines and were dominated by young males belonging to high socio-economic groups. These results also agreed with previous studies (Wijaya and Polina, 2014;Kapondera, 2014;Kapondera and Chigona, 2017) and recent studies (Mudliar, 2018;Alao et al, 2022) that have asserted that women are restrained by social norms. Internet facilities are limited for women as compared to men (Alao et al, 2022).…”
Section: Introductionsupporting
confidence: 93%